2017
DOI: 10.5194/isprs-archives-xlii-3-w3-137-2017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Various Remote Sensing Technologies in Biomass and Nitrogen Content Estimation Using an Agricultural Test Field

Abstract: ABSTRACT:Multispectral and hyperspectral imaging is usually acquired by satellite and aircraft platforms. Recently, miniaturized hyperspectral 2D frame cameras have showed great potential to precise agriculture estimations and they are feasible to combine with lightweight platforms, such as drones. Drone platform is a flexible tool for remote sensing applications with environment and agriculture. The assessment and comparison of different platforms such as satellite, aircraft and drones with different sensors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…We also evaluated the impact of the radiometric processing level on the results. This paper extends our previous work [55], which performed a preliminary study with the barley data using linear regression techniques. The major contributions of this study were the development and assessment of the integrated use of spectral and 3D features in the crop parameter estimation in different conditions, the comparison of RGB and hyperspectral imaging based remote sensing techniques and the consideration of impacts of various parameters, especially the flying height and the radiometric processing level on the results.…”
Section: Introductionsupporting
confidence: 57%
“…We also evaluated the impact of the radiometric processing level on the results. This paper extends our previous work [55], which performed a preliminary study with the barley data using linear regression techniques. The major contributions of this study were the development and assessment of the integrated use of spectral and 3D features in the crop parameter estimation in different conditions, the comparison of RGB and hyperspectral imaging based remote sensing techniques and the consideration of impacts of various parameters, especially the flying height and the radiometric processing level on the results.…”
Section: Introductionsupporting
confidence: 57%
“…Dry Biomass (DBM) in g/m 2 : for DBM retrieval, the GPR model is selected with the most relevant bands being the blue, green, middle red-edge and near infrared (λ = 560; 740; 490; 842). In related studies [3,7,40,41] it was found that for crops or grass, DBM is best retrieved with visible and near-infrared reflectance which is in accordance with our results.…”
Section: Selected Model For Each Variablesupporting
confidence: 92%
“…The drone-based photogrammetric point clouds have also shown potential in agricultural crop biomass estimation (eg. Bendig et al, 2013;Li et al, 2016;Näsi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%